Pre-steady-state kinetics and solvent isotope effects support the "billiard-type" transport mechanism in Na+-translocating pyrophosphatase - Malinen Anssi M; Anashkin Viktor A; Orlov Victor N; Bogachev Alexander V; Lahti Reijo; Baykov Alexander A (WILEY, 2022)
Membrane-bound pyrophosphatase (mPPase) found in microbes and plants is a membrane H+ pump that transports the H+ ion generated in coupled pyrophosphate hydrolysis out of the cytoplasm. Certain bacterial and archaeal mPPases can in parallel transport Na+ via a hypothetical "billiard-type" mechanism, also involving the hydrolysis-generated proton. Here, we present the functional evidence supporting this coupling mechanism. Rapid-quench and pulse-chase measurements with [P-32]pyrophosphate indicated that the chemical step (pyrophosphate hydrolysis) is rate-limiting in mPPase catalysis and is preceded by a fast isomerization of the enzyme-substrate complex. Na+, whose binding is a prerequisite for the hydrolysis step, is not required for substrate binding. Replacement of H2O with D2O decreased the rates of pyrophosphate hydrolysis by both Na+- and H+-transporting bacterial mPPases, the effect being more significant than with a non-transporting soluble pyrophosphatase. We also show that the Na+-pumping mPPase of Thermotoga maritima resembles other dimeric mPPases in demonstrating negative kinetic cooperativity and the requirement for general acid catalysis. The findings point to a crucial role for the hydrolysis-generated proton both in H+-pumping and Na+-pumping by mPPases.